City-State (Medina) and Its Implementation in the Republic of Indonesia - Agus Nurhakim (UIN Sunan Gunung Djati Bandung, 2016)
This article describes on how the principle of the Islamic State concerned with Indonesia as a nation state. State elements theory explains that the country is composed of three elements such as the region, the people, and the government as well as the sovereignity. By using the literature study, this article found that the Prophet Muhammad is a leader who always carries his reign by implementing the principles of Islam as well. Among the principles of the state in Islamic perspective consists of the trust, consultation, fairness, freedom, and equality. Relating to this reason, the Indonesian state is seen as the state of law because it refers to the 1945 Indonesia Constitution (UUD 1945) and Pancasila. Shortly, Indonesia is in need of having the people who has the responsibility and trusted in maintaining this country.